Copper(II)‐Catalyzed Asymmetric 1, 3‐Dipolar [3+4] Cycloaddition and Kinetic Resolution of Azomethine Imines with Azoalkenes. Issue 24 (25th November 2016) - Wei, Liang; Wang, Zuo‐Fei; Yao, Lu; Qiu, Guofu; Tao, Haiyan; Li, Hua; Wang, Chun‐Jiang
Abstract: An unprecedented copper(II)‐catalyzed enantioselective 1, 3‐dipolar [3+4] cycloaddition of azomethine imines with in situ formed azoalkenes has been realized. This strategy provides a facile access to biologically important 1, 2, 4, 5‐tetrazepine derivatives in high yield with exclusive regioselectivity and high stereoselectivity. Moreover, enantioenriched azomethine imines could be obtained via an efficient kinetic resolution using the same approach. Abstract :